2017
DOI: 10.1021/acs.orglett.7b02288
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylamino Pyrimidyl Amides (MAPA): Highly Reactive, Electronically-Activated Amides in Catalytic N–C(O) Cleavage

Abstract: Despite recent progress in catalytic cross-coupling technologies, the direct activation of N-alkyl-N-aryl amides has been a challenging transformation. Here, we report the first Suzuki cross-coupling of N-methylamino pyrimidyl amides (MAPA) enabled by the controlled n → π conjugation and the resulting remodeling of the partial double bond character of the amide bond. The new mode of amide activation is suitable for generating acyl-metal intermediates from unactivated primary and secondary amides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…We found that a combined N-carbamate and N-Ts or N-Ac activation results in a near perpendicular twist of the amide bond in simple acyclic amides (τ = 87.2 • ). These amides for the first time matched the distortion achieved in bridged lactams [83] We further went on to demonstrate the use of N-methylaminopyrimidyl-amides (MAPA) for the acyl Suzuki cross-coupling (Scheme 25B) [91]. With the use of (IPr)Pd(cinnamyl)Cl precatalyst this reaction occurs with high acyl N-C activation chemoselectivity.…”
Section: Suzuki Cross-coupling Of Amidesmentioning
confidence: 89%
See 1 more Smart Citation
“…We found that a combined N-carbamate and N-Ts or N-Ac activation results in a near perpendicular twist of the amide bond in simple acyclic amides (τ = 87.2 • ). These amides for the first time matched the distortion achieved in bridged lactams [83] We further went on to demonstrate the use of N-methylaminopyrimidyl-amides (MAPA) for the acyl Suzuki cross-coupling (Scheme 25B) [91]. With the use of (IPr)Pd(cinnamyl)Cl precatalyst this reaction occurs with high acyl N-C activation chemoselectivity.…”
Section: Suzuki Cross-coupling Of Amidesmentioning
confidence: 89%
“…We further went on to demonstrate the use of N-methylaminopyrimidyl-amides (MAPA) for the acyl Suzuki cross-coupling (Scheme 24B) [91]. With the use of (IPr)Pd(cinnamyl)Cl precatalyst this reaction occurs with high acyl N-C activation chemoselectivity.…”
Section: Suzuki Cross-coupling Of Amidesmentioning
confidence: 99%
“…In 2017, Szostaka nd co-workersr eported aP d ÀNHC-catalyzed Suzuki coupling reaction of electronically activated Nmethylamino pyrimidyl amides (MAPAs) through NÀCa ctivation (Scheme 39). [77] The notable advantages of this method were its operationally simplep rocedure,t he facile preparation of MAPAfrom primary or secondary amides, and the avoidance of phosphine-based ligands. Thes ubstrate scope for the boronic acid and amide components wase valuated and both electron-donating and electron-withdrawingd erivatives were tolerated, therebya ffording the products in goodto-excellent yields.…”
Section: Cross-coupling and Other Reactionsmentioning
confidence: 99%
“…To date, a wide range of amides and amide-based reagents, including the most reactive N-acyl-glutarimides [13] as well as anilides [14], N-Boc-carbamates [15], N-Ts-sulfonamides [16], N, N-di-Boc amides [17], N-acyl-saccharins [18,19], N-Ms-sulfonamides [20], N-acyl-pyrroles [21], N-Me-pyrimidines [22], N-acyl-succinimides [23][24][25], and N-Ac-amides [26] have been successfully engaged as electrophilic cross-coupling partners by N-C activation. In all examples described to date, the reactivity has been controlled by a ground-state destabilization mechanism of the amide bond [12].…”
Section: Introductionmentioning
confidence: 99%